Marketing Audit and Its Importance in Achievement of Marketing Objectives of a Company - GÂDĂU, Liana (Journal of Advanced Research in Management; Vol 8 No 1 (2017): JARM Volume VIII Issue 1(15) Summer 2017DO - 10.14505//jarm.v8.1(15).04, 2017)
The concept of marketing audit is currently highly discussed. The main purpose of this paper is to support implementation of marketing audit in activity of companies. The importance and using of marketing audit is growing and companies realize its importance for their future growth and success. The paper deals with marketing audit and the importance of valued information which can contribute to the detection of opportunities and threats in the market. Through this paper we would like to bring into focus the broad and different aspects of marketing audit that can help an organization to understand the internal as well as external environment thus effectively analyzing its strategies and their implementation. Marketing audit is the most important step in the development of the marketing Plan. Marketing audit has an essential contribution to the future success of the business. Depending on the results of marketing audit is drafted the plan and marketing strategy that will be applied later. Final goal of marketing audit is elaborating a strategy in accordance with the company's real problems.